2022
DOI: 10.1002/jlb.3ma0422-742r
|View full text |Cite
|
Sign up to set email alerts
|

Contact-dependent, polarized acidification response during neutrophil–epithelial interactions

Abstract: Inflammatory acidosis represents a polarized neutrophil-epithelial-dependent response independent of myeloperoxidase and ion efflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…Recently, it has been observed that PMN-epithelial interaction results marked inflammatory acidification that was dependent on PMN-epithelial contact, but independent of PMN transepithelial migration. The source of the acidification was identified to be the epithelial cells and is a result of increased lactic acid production and increased ROS generation during PMN-epithelial cell interactions ( 20 , 73 ).…”
Section: Tissue Acidification and Ph Regulationmentioning
confidence: 99%
“…Recently, it has been observed that PMN-epithelial interaction results marked inflammatory acidification that was dependent on PMN-epithelial contact, but independent of PMN transepithelial migration. The source of the acidification was identified to be the epithelial cells and is a result of increased lactic acid production and increased ROS generation during PMN-epithelial cell interactions ( 20 , 73 ).…”
Section: Tissue Acidification and Ph Regulationmentioning
confidence: 99%